2014
DOI: 10.1111/bjd.13165
|View full text |Cite
|
Sign up to set email alerts
|

Trichophyton rubrumDNA strain switching increases in patients with onychomycosis failing antifungal treatments

Abstract: Nine T. rubrum DNA strains were identified in a North American population: three novel and six predominant to a European population. Although DNA strain type switching in onychomycosis is a natural phenomenon, with presence in the placebo group, increases following the course of failed onychomycosis treatment suggest an antifungal-induced response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…It is highly recommended that, if the first test is positive for an NDM, additional patient sampling be undertaken on a minimum of two separate occasions before initiating treatment, and direct microscopy examination be included in the full mycological evaluation, as recommended for confirmation of NDMs as etiological agents [5,19,20]. It is noteworthy that terbinafine resistance is rare in dermatophytes [21,22] and a logical explanation for apparently failed terbinafine treatments of dermatophyte infections could be the presence of a mixed dermatophyte-NDM infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly recommended that, if the first test is positive for an NDM, additional patient sampling be undertaken on a minimum of two separate occasions before initiating treatment, and direct microscopy examination be included in the full mycological evaluation, as recommended for confirmation of NDMs as etiological agents [5,19,20]. It is noteworthy that terbinafine resistance is rare in dermatophytes [21,22] and a logical explanation for apparently failed terbinafine treatments of dermatophyte infections could be the presence of a mixed dermatophyte-NDM infection.…”
Section: Discussionmentioning
confidence: 99%
“…First, strain typing of T. rubrum was performed by Southern blot hybridization based RFLP analysis, 17 the method used in the most recent study which found the strain switching in patients with onychomycosis. 18 Then, species-specific PCR primers targeting tandemly repetitive subelements in NTS (TRS-1, TRS-2) were synthesized to detect interspecies variations. Assays of TRS-1 and TRS-2 polymorphisms in 101 clinical isolates identified 23 separate PCR types, 19 with these markers later used to identify species and subspecies of T. rubrum.…”
Section: Non-transcribed Spacer Regions Of Rdnamentioning
confidence: 99%
“…Trichophyton rubrum is the most prevalent dermatophyte, accounting for about 80% of dermatomycoses that affect keratinized tissues such as skin, hair, and nails [ 1 ]. Moreover, these infections play an important role in the scenario of opportunistic infections in immunocompromised patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%